OPTN/SRTR 2019 Annual Data Report: Kidney. Issue 2 (17th February 2021) - Hart, A.; Lentine, K. L.; Smith, J. M.; Miller, J. M.; Skeans, M. A.; Prentice, M.; Robinson, A.; Foutz, J.; Booker, S. E.; Israni, A. K.; Hirose, R.; Snyder, J. J.
Abstract: Despite the ongoing severe shortage of available kidney grafts relative to candidates in need, data from 2019 reveal some promising trends. After remaining relatively stagnant for many years, the number of kidney transplants has increased each year since 2015, reaching the highest annual count to date of 24, 273 in 2019. The number of patients waiting for a kidney transplant in the United States was relatively stable, despite an increase in the number of new candidates added in 2019 and a decrease in patients removed from the waiting list owing to death or deteriorating medical condition. However, these encouraging trends are tempered by ongoing challenges. Nationwide, only a quarter of waitlisted patients receive a deceased‐donor kidney transplant within 5 years, and this proportion varies dramatically by donation service area, from 15.5% to 67.8%. The non‐utilization (discard) rate of recovered organs remains at 20.1%, despite adramatic decline in the discard of organs from hepatitis C‐positive donors. Non‐utilization rates remain particularly high for Kidney Donor Profile Index ≥85% kidneys and kidneys from which a biopsy specimen was obtained. While the number of living‐donor transplants increased again in 2019, only a small proportion of the waiting list receives living‐donor transplants each year, and racial disparities in living‐donor transplant access persist. As both graft and patient survival continue to improve incrementally, the total number of living kidney transplant recipients with a functioning graft is anticipated to exceed 250, 000 in the next 1‐2 years. Over the past decade, the total number of pediatric kidney transplants performed has remained stable. Despite numerous efforts, living donor kidney transplant remains low among pediatric recipients with continued racial disparities among recipients. Congenital anomalies of the kidney and urinary tract remain the leading cause of kidney disease. While most deceased donor recipients receive a kidney from a donor with KDPI less than 35%, the majority of pediatric recipients had four or more HLA mismatches. Graft survival continues to improve with superior outcomes for living donor recipients.